Mapping the Development of Halal Awareness Research: A Bibliometric Analysis - Nurul Halimah; Muthoifin (Walidem Institute and Publishing (WIP), 2026)
Objective: The study aims to analyze the development of halal awareness and consumer behavior through a bibliometric approach focusing on halal food and beverage literature in the global research landscape. Theoretical framework: The theoretical framework is grounded in consumer behavior theory and halal compliance concepts, emphasizing awareness perception and decision-making in Muslim consumption contexts. Literature review: The literature review highlights increasing scholarly attention on halal awareness driven by globalization, a rising Muslim population, and demand for ethically compliant products across sectors. Methods: This study employs a bibliometric analysis using the Scopus database comprising 243 documents and utilizes VOSviewer software to map research networks, co-authorship patterns, and thematic trends. Results: The results reveal significant growth in publications, influential authors leading journals, and dominant research clusters focusing on halal consumer behavior certification and awareness trends across countries. Keywords: consumer behavior, halal awareness, bibliometric analysis. Furthermore, the analysis identifies research gaps in underexplored regions and interdisciplinary collaborations, suggesting opportunities for future studies integrating digital transformation and halal industry innovation. In addition, citation analysis shows that certain authors and journals dominate the intellectual structure of halal awareness research, indicating consolidation of knowledge within specific academic communities. The study also demonstrates increasing collaboration networks among international researchers, reflecting the global nature of halal consumption studies. These patterns indicate the growing interdisciplinarity of halal research combining economics, marketing, and religious studies. Overall, this bibliometric mapping contributes to a deeper understanding of the evolution of halal awareness scholarship worldwide, providing a structured reference for future halal awareness research development strategies and policy formulation processes improvement. Implications: The findings imply that halal awareness research provides valuable insights for policymakers, industry stakeholders, and academics in strengthening halal ecosystem development and consumer trust. Novelty: The novelty of this study lies in its comprehensive mapping of bibliometric indicators combined with trend forecasting and identification of emerging topics in halal awareness research.